Parents and Caregivers Satisfaction After Palliative Treatment of Spastic Hip Dislocation in Cerebral Palsy - Koch, Aleksander; Krasny, Joanna; Dziurda, Magdalena; Ratajczyk, Magdalena; Jozwiak, Marek (Frontiers in Neurology, 2021)
Pain appearance is one the most common complication of spastic hip disease in cerebral palsy children. We would like to present four palliative methods of spastic hip dislocation treatment in CP children. Material and Method: four groups of patients: 1.steroid injections to hip joints, 2. hip interposition arthroplasty with shoulder spacer, 3. valgus subtrochanteric femoral osteotomy (Schanz), 4. proximal femoral resection (Castle procedure). Inclusion criteria were pain appearance (VAS-11 or NRS-11) and hip joint dislocation. The minimal follow up time was 2 years. The first group consisted of 15 patients (15 hips) age 15,5(8-17), the second group 20 patients (24 hips) age 14,2(9-22,6), the third group 22 patients (24 hips) age 13,5(7-20,5) and the fourth group 10 patients (15 hips) age 12,9(7-17,6). Parents were asked about their child pain and about treatment satisfaction (0-10). Results: we observed decrease of pain. In the first group it was from 7,88(4-10) to 3,08(0-8) (p=0.05) results of injection was observed for 4 months (2-8) and it has to be repeated( av.2 times). In the second group from 4,93(1-10) to 0,93(0-5) (p<0.001), in the third group from 6,22(3-10) to 0,59(0-6) (p<0.001), in the fourth group from 5,43(2-10) to 2.13(0-5) (p<0.001) Observed changes concerned mostly sitting position and perineal care. Complication rate was in the second group 6 extraarticular ossification, in third group 2 extraarticular ossification, 2 revision surgery. In fourth group 2 needed another femoral resection. In the steroid injection group parents treatment evaluation was 6.83 (0-10), In the hip interposition arthroplasty was 7,41 (0-10), In Schanz group was 5,9 (0-10) and In resection group was the highest 8,3 (3-10). Conclusion: All procedures can be consider as palliative treatment options for pain complain in spastic hip joint dislocation in CP children. Steroid injections to hip joint needs to be repeated and it becomes less effective. Steroid injection seems to be treatment of choice for patients with general anestesia contraindications. Interposition arthroplasty of the hip joint seems to give better final results but the highest parents satisfaction surprisingly was observed in proximal femoral resection group but differences were not statistically significant.